A new genus and four new species of Darnini (Hemiptera: Membracidae) from South America - González-Mozo, Laura; Mckamey, Stuart H. (Zootaxa, 2024)
The new genus Polyodontotrochus is described and illustrated with four new species: P. auriculatus from French Guiana, P. elevatus (type species) from Ecuador, P. extentapalaestrus from French Guiana, and P. inpa from Brazil, the genus differs from all other membracids in having the inner sides of their metathoracic trochanters developed into apposed, sclerotized studlike, flattened plates distributed throughout. Their metathoracic tibiae have cucullate setal rows II and III incomplete, row I missing. A key to all species is provided.